First description of Cryptosporidium parvum in carrier pigeons (Columba livia) - Oliveira, Bruno César Miranda [UNESP] (2017)
The carrier pigeon and the domestic pigeon are different breeds of the species Columba livia. Carrier pigeons are used for recreational activities such as bird contests and exhibitions. Due to the close contact with humans, these birds may potentially represent a public health risk, since they can host and disseminate zoonotic parasites, such as those belonging to the genus Cryptosporidium (phylum Apicomplexa). The purpose of this work was the detection by microscopic and molecular techniques of Cryptosporidium spp. oocysts in fecal samples of carrier pigeons, and subsequently to sequence the 18S ribosomal RNA marker of positive samples to identify the species. A total of 100 fecal samples were collected individually in two pigeon breeding facilities from Formiga and Araçatuba, cities located in Minas Gerais state and São Paulo state, Brazil, respectively. The age of the birds ranged from one to 12 years; 56 were females and 44 males. Fecal smears were stained with negative malachite green, whereas the molecular characterization was based on the sequence of a ∼800 bp fragment of the 18S rRNA gene. Microscopic examination of fecal smears revealed 4% (4/100) oocyst positivity. On the other hand, 7% (7/100) of positivity were found using nested PCR. Three samples were 99% to 100% similar to Cryptosporidium parvum 18S rDNA type A (Genbank AH006572) and the other three samples had 99% to 100% similarity to C. parvum 18S rDNA type B (Genbank AF308600). To our knowledge, this is the first report of C. parvum oocysts in carrier pigeons.